Trends and insights in non-alcoholic fatty liver disease (NAFLD) and cognition research - Anam Rehman; Azidah Abdul Kadir; Rahimah Binti Zakaria; Nik Hazlina Binti Nik Hussain (Journal of University Medical & Dental College, 2025)
Currently, wide range of experimental exploration on NAFLD engraved our brains that this disease is spreading at its rapid pace. This experimentation has covered researches of decades till 2023, determining the burden of disease on society. It included 243 articles which were targeted using the keywords linked to NAFLD and cognition. VOS software viewer was used, generating a linkage among author keywords. It showed that the utmost work in this domain is contributed by United States, making it the top contributor. Distinguished keywords involve "metabolic regulation," "metabolic comorbidity," "metabolic hepatopathy," "liver and psychological health," All these themes communally increases our understanding in the regard of complicated links among lifestyle, genetics, liver health, and cognition inside the framework of NAFLD. These findings suggests valuable understanding for emerging all-inclusive healthcare approaches addressing physical and mental well-being.